In Vivo Testing of Pseudozyma hubeiensis to Control Aspergillus flavus in Nutmeg Seeds (Myristica fragrans Houtt.) - Rahayuningsih, Sri; Hidayah, Mudrikah Nurul; Susilowati, Dwi Ningsih; Supriadi; Suryadi, Yadi; Rismayani; Radiastuti, Nani (Al-Kauniyah: Jurnal Biologi, 2026)
Nutmeg (Myristica fragrans Houtt.) is a high-value spice commodity from Indonesia, often contamination with aflatoxin-producing Aspergillus flavus. Previous research has identified two epiphytic yeast isolates from nutmeg plants, namely DP1341a and DP1342, both of which were identified as Pseudozyma hubeiensis and showed antagonistic potential against A. flavus. This study is a follow- up study that aims to test the antagonistic activity of both isolates against A. flavus in vivo on nutmeg seeds. The research was conducted experimentally through several stages, namely testing the compatibility of isolates on Yeast Malt Agar (YMA) media, determining the optimum fermentation time, and applying liquid culture and fermentation filtrate to 120 nutmeg seeds. Results showed that the consortium of isolates DP1341a and DP1342 did not increase the inhibitory power results compared to single cultures with optimum fermentation times of 10 and 14 days, respectively. In vivo applications show that treatment with DP1342 isolate (KC-DP1342) and consortium in liquid culture provides the highest level of resistance to A. flavus infection, namely 38.67% and 28.00%. The findings suggest that P. hubeiensis DP1342 has potential as a biological control agent in controlling A. flavus on nutmeg seeds, although further formulation and optimization are needed.